SARS-CoV-2 vaccine rollout campaigns - Graca, Luis (Henry Stewart Talks, 2021)
Overview on vaccine campaign strategies, Challenges in a SARS-CoV-2 vaccine campaign strategy, Identification of priority groups, Difficulties of including priority groups into a vaccine campaign